PEMODELAN VECTOR AUTOREGRESSIVE EXOGENOUS (VARX) UNTUK MERAMALKAN DATA EKSPOR TOTAL DAN IMPOR TOTAL DI INDONESIA - Salsabila, Nur Afifah; Wahyuningsih, Sri; Purnamasari, Ika (Jambura Journal of Probability and Statistics, 2022)
Vector Autoregressive Exogenous (VARX) is a multivariate time series model which is a development of the Vector Autoregressive (VAR) model. VARX model is a forecasting model that involves endogenous variables and exogenous variables. The endogenous variables in this study are exports and total imports in Indonesia, then the exogenous variable in this study is the composite stock price index in Indonesia. The purpose of this study is to VARX model the export and total import data in Indonesia for the period January 2016 to December 2021 and predict it for the period January 2022 to December 2022. Based on the result of the analysis, the best model for forecasting export and total imports is the VARX(2.2) model with the MAPE value for the total export variable of 5.938% and the total import variable of 8.313%. Furthermore, the results of forecasting total exports have increased in the period January 2022 to December 2022, with forecasting results for January 2022 of US$21,383.06 million and December 2022 of US$23,569.50 million. The results of forecasting total imports have increased in the period January 2022 to December 2022, with forecasting results in January 2022 of US$17,743.17 million and December 2022 of US$20,269.07 million.